Role of Financial Performance of Global Islamic and Conventional Microfinance Institutions in Sustainable Development Goals Achievement - Noor, Amat-ul Mateen; Ayaz, Mohammad (iRASD Journal of Economics, 2023)
The achievement of sustainable development goals is a challenge for United Nations Development Programme member countries. Therefore, the purpose of this research was to explore and compare the role that the financial performance of global Islamic and conventional microfinance institutions playing achieving sustainable development goals by using non-traditional indexes. Further, the study also checked the moderating role of institution size in this relationship. Results indicate that the financial performance of both Islamic and conventional microfinance institutions is important to achieving sustainable development goals. Institution size as a moderator has a negative impact on the financial performance of conventional microfinance institutions in achieving sustainable development due to the possibility of commercialization. In terms of policy recommendations, the results of this study present several policy directions for both Islamic and conventional institution managers for both developed and developing countries. Both Islamic and conventional MFIs managers should focus on financial performance to achieve sustainable development goals. The managers should realize that in the case of increasing the institution's size, financial performance can be improved, but it also creates commercialization, making the main objective of serving the poorest customers difficult. This study also gives directions to the government, central bodies, and other regulatory authorities to develop policies for improving the financial performance of both Islamic and conventional microfinance institutions to achieve sustainable development goals. This study has taken two indicators of financial performance that are extensively discussed in the literature. For future studies, other financial performance indicators can be included in the study.